Forensic profiling of heroin seized from northern region of Malaysia - Yusoff, Mohd Zawawi (2017)
A strategic location connecting the Golden Triangle or Afghanistan has prompted Malaysia as a transit hub for trafficking activities of illicit drugs. An increasing source of illicit heroin, originating from these regions, has been transhipped to other parts of Asia and also Oceania countries. Therefore, forensic drug profiling could provide useful information on the trafficking routes and the origin of drugs for intelligence purpose. This study is aimed at establishing the possible relationship among the heroin samples seized from different sources for predicting the trafficking network of illicit heroin in northern region of Malaysia. One hundred and fifty-five seized heroin samples were examined physically to determine their colours and texture. Colour tests, namely Marquis, Foerhde, Janovsky dan Simon’s were used for screening purposes. Subsequently, all seized drug samples were analysed using three analytical techniques, namely Attenuated Total Reflectance-Fourier Transform Infra-red spectroscopy (ATR-FTIR), Gas Chromatography-Flame Ionisation Detection (GC-FID) and Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The analytical results were subjected to chemometric procedures for chemical profiling and subsequently cluster the seized heroin samples into possible groups. In this study, physical examination showed the appearance of four different colours and three varying textures among the seized samples. The positive reactions on Marquis and Foerdhe Reagents have shown the potential presence of opiate related substances, including heroin. An optimised and validated GC-FID method was used to analyse the samples. The method allowed rapid analysis of heroin samples within approximately 12 minutes per run, thus enabled simple, precise and accurate analysis in highthroughput procedure often encountered in Narcotic Laboratory. The presence of heroin was confirmed by using Gas Chromatography-Mass Spectrometry. Additional to GC analysis, ICP-MS has enabled the quantitation of trace elements in the seized samples. Trace elements present in seized heroin samples could be due to contamination from processing methods, cooking utensils and chemicals used during cutting and packaging process. Results of FTIR analysis were subjected to principal component analysis that revealed the formation of four different clusters of illicit heroin, namely samples of high purity, samples cut with polysaccharide and caffeine, as well as samples of very low purity. Hierarchy Cluster Analysis following the FTIR analysis allows the discrimination of drug samples into ten subclusters with the possibility of attributing similar refining process or cutting pattern during drug trafficking. In general, heroin samples seized from central regions of Malaysia gave significantly different profiles, separating them from those obtained in northern region. Chemometrics are good exploratory methods to extract information about the origin of seized heroin sample and their distribution chains. This comparative information offers beneficial forensic intelligence to help establish the existence of different clusters of trafficking network.